A new species of Lassenia (Acari: Tanaupodidae) from Turkey - Javad Noei; Emre Inak; Sultan Çobanoğlu; Alireza Saboori (Persian Journal of Acarology)
Lassenia hemsinensis Noei, Saboori & Çobanoğlu sp. nov. (Acari: Trombidiformes: Tanaupodidae) collected from Hemşin, Rize, Turkey, on Rumex sp. (Polygonaceae) (off host) is described. A key to the species of Lassenia (larva) of the world is also provided.